Vaccine Hesitancy in Japan: From a Perspective on Medical Uncertainty and Trans-Scientific Theory [version 2; peer review: 2 approved, 1 approved with reservations] - Miwako Hosoda (F1000Research, 2023)
The development and dissemination of vaccines has made immunization possible and has led to the successful control and eradication of various infectious diseases in many parts of the world. However, even when vaccines that are said to be "effective" are offered, a certain number of people do not receive them, and this has become a problem known as "vaccine hesitancy”. ItThe reason of “Vaccine hesitancy” is pointed out that there is not only because of the risk of contracting infectious diseases if they are not vaccinated, but also because of the lack of a collective immunity system. Vaccines are an effective means of acquiring immunity, but no matter how highly effective vaccines are developed, if the vaccination rate does not exceed a certain number, “herd immunity”, which means that the risk of person-to-person transmission is reduced when a significant portion of the population becomes immune to, cannot be acquired. Therefore, how to increase the vaccination rate of the population is a major public health challenge. This paper reviews previous studies on "vaccine hesitancy" in Japan and analyzes people's hesitancy in terms of negative "rumors" about vaccines, risk perception of vaccine side effects, and sense of burden when receiving vaccinations. Then, the author will examine that the background of "vaccine hesitancy" is not only distrust of vaccines and risk perception of side effects, but also distrust of those who provide and promote vaccinations, such as medical professionals, government, and public administration. By using medical uncertainty which shows there are many unknowns and uncertainties in medicine and trans-scientific theory which indicates there are areas that science cannot answer this paper argues that the problem of "vaccine hesitancy" can be reduced if medical professionals and governments show sincere empathy and attitude toward victims of adverse vaccine reactions and those who hesitate to vaccinate.